CTA634 : Advances 3D computer animation / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course is an extension course of Computer Animation: Intermediate course which emphasizes on applying details into 3D character animation. Students will learn to integrate the 12 principles of animation into animated character and learn the technical features of 3D animation software technique and tools upon producing a vibrant and unique perspective of animated character project.